Myocardial Infarction in the Young: Aetiology, Emerging Risk Factors, and the Role of Novel Biomarkers - Mithila Zaheen; Patrick Pender; Quan M. Dang; Eva Sinha; James J. H. Chong; Clara K. Chow; Sarah Zaman (Journal of Cardiovascular Development and Disease)
Despite significant advancements in the primary and secondary prevention of cardiovascular disease, evidence shows a rising incidence of premature coronary artery disease (CAD) and myocardial infarction (MI) in patients aged < 50 years. This increase is linked to the growing prevalence of traditional cardiovascular risk factors among younger people, such as type 2 diabetes, hypertension, obesity, and hyperlipidaemia, which have led to a rise in atherosclerotic CAD. Additionally, emerging research points to the influence of less traditional risk factors, including chronic inflammation, autoimmune diseases, drug use, psychosocial factors, and novel biomarkers in the early onset of CAD. These factors collectively contribute to the rise in premature CAD, highlighting the need for improved prevention strategies and public health efforts focused on younger populations. In this review, we explore the aetiology, risk factor profile, role of novel biomarkers, and how each of these impact outcomes among younger patients with MI.